Computer simulation method for moving trajectories of biological particles in rotating vertebral bodies - Cong Ling Zhu; Chang Chang Li; Ye Ye Weng (The Journal of Engineering, 2020)
Biomass fuel production has a variety of methods, and the use of biomass cracking to produce biofuels is an advanced technology used in many countries. In the control of the biofuel production process, how to get the motion law of the heat carrier in the cone relative to the cone becomes a problem that must be solved. This study uses the basic theory of dynamics and computer simulation calculation function to carry out dynamic analysis of each of the above contents, and analyses the response problem of comprehensive factors, and obtains the simulation results in accordance with the experimental results. This analysis provides a detailed design rationale for the optimal design of biomass cone pyrolysis equipment.